2012
DOI: 10.1258/ebm.2012.012135
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th1 immune response in SERPINB3 transgenic mice during acute liver failure

Abstract: Acute liver failure (ALF) is characterized by severe neurological complications, known as acute hepatic encephalopathy, where brain ammonia and inflammatory processes play a dominant role. In experimental models of acute liver failure SERPINB3 was found significantly increased in microglia, the intrinsic immune cells of the central nervous system. The aim of the present study was to investigate the extent of brain tissue damage and the inflammatory milieu in experimental acute liver failure using a SERPINB3-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…[23][24][25][26] High SB3 levels have been recently detected in HCC tissue of patients with early tumour recurrence after surgical resection, suggesting their involvement in liver malignancy. [23][24][25][26] SB3 is expressed in human liver progenitor cells, 27 as indicated by its detection in EpCAM + cell fractions sorted from human foetal and adult livers and in ductular liver structures expressing stem/ progenitor cell markers. Furthermore, the mouse homologous, SerpinB3b, was induced by the administration of lipopolysaccharide and D-galactosamine, a model of liver stem/progenitor cell activation.…”
Section: Lay Summarymentioning
confidence: 99%
“…[23][24][25][26] High SB3 levels have been recently detected in HCC tissue of patients with early tumour recurrence after surgical resection, suggesting their involvement in liver malignancy. [23][24][25][26] SB3 is expressed in human liver progenitor cells, 27 as indicated by its detection in EpCAM + cell fractions sorted from human foetal and adult livers and in ductular liver structures expressing stem/ progenitor cell markers. Furthermore, the mouse homologous, SerpinB3b, was induced by the administration of lipopolysaccharide and D-galactosamine, a model of liver stem/progenitor cell activation.…”
Section: Lay Summarymentioning
confidence: 99%
“…It is also capable to induce epithelial–mesenchymal transition, with increased invasiveness potential , and to induce TGF‐beta . A recent study in a mouse model of acute liver failure has demonstrated that the presence of SERPINB3 determines an enhanced inflammatory background, mainly mediated by higher levels of Th1 proinflammatory cytokines . At the serological level, high or increasing levels of SCCA‐IgM immune complexes were associated with more advanced liver disease and increased risk of HCC development .…”
Section: Introductionmentioning
confidence: 99%
“…5 Summary of the study design. The figure depicts the benchmark for the identification and validation of candidate pathogenic factors and how they can be distinguished from bystander biomarkers in the present study Despite A1at-SerpinB3 TG mice having several pathological and non-pathological features comparable with those of WT mice [21][22][23], including an increased lifespan [24], we did not find any difference in the wound healing process. This indicates that, at least in this experimental model, a high serpinB3 level is in itself insufficient to improve wound healing and seems to argue against a direct role for serpinB3 in the healing process.…”
Section: Discussionmentioning
confidence: 66%
“…[20]. It has been previously shown to be involved in wound healing processes, including epithelial-to-mesenchymal transition [21], inflammation [22] and apoptosis [23]. Proteomic data, as well as gene and protein analysis, showed higher levels of serpinB3 in RH compared with NH wounds.…”
Section: Discussionmentioning
confidence: 96%